Ophthalmology Residency Virtual Interviews in the Setting of the COVID-19 Pandemic: Perspectives of Applicants, Selection Committee Members, and Current Residents - Abigail Jebaraj (Thieme Medical Publishers, Inc., 2021)
Background In the setting of the COVID-19 pandemic, residency programs implemented videoconferencing “virtual” interviews for the 2020 to 2021 match cycle. There is limited published information on virtual ophthalmology residency interviews. Objective The study aimed (1) to assess applicant, selection committee member, and resident opinions of technical quality, communication quality, and ability to assess applicant or program “fit” during virtual interviews; (2) to determine which interview format—in-person or virtual—each party would prefer in the future; and (3) to survey which residency resources applicants found helpful. Design Surveys were sent to applicants, selection committee members, and residents to assess the above objectives for the 2020 to 2021 match cycle virtual interviews at the Moran Eye Center, University of Utah. Setting This study was conducted in a single residency program interview season from 2020 to 2021. Participants Forty applicants, eight committee members, and seven residents who participated in the virtual interview process were surveyed. Intervention or Exposure Prior to interviews, various avenues were implemented to connect with applicants. A videoconferencing software was utilized for interviews. Applicants and selection committee members met in one-on-one or small group interviews. Residents communicated with applicants in a large group setting between interviews. Main Outcome and Measure The study aims to survey the participants as stated in the objectives. There was no planned outcome for this quality improvement study. Results Survey response rate was 98.2% (54/55). All parties rated the technical components as good or very good. Applicants and selection committee members rated communication as overall good or very good, although residents thought communication was very poor. A total of 92.3% applicants, 75% selection committee members, and 0% residents were reported that they were able to appropriately assess fit of the program with the applicant. However, 46.3% respondents preferred in-person interviews in the future. Popular applicant resources were resident-produced videos (82.1%), conversations with residents (46.2%), and a gift bag (43.6%). Conclusion and Relevance Overall, the technical components of the interview were successful. Small, structured group interactions led to better communication and assessment of fit. There were variable opinions regarding future interview format preference between in-person, virtual, or choice. Amid the COVID-19 pandemic, connecting with applicants via various means can optimize the match process.